Morphological, Structural, and Physicochemical Properties of Starch in Hybrids and Inbred Lines from Sweet–Waxy Maize. (10th June 2021) - Hu, Yifan; Wang, Jun; Chi, Ming; Yang, Siling; Lu, Dalei
Abstract: Sweet–waxy maize is a special type of maize with recessive mutations of waxy gene and a gene disturbed sugar‐starch transition, and its starch is composed of nearly pure amylopectin. The starch physicochemical properties of four inbred lines and six hybrids of sweet–waxy maize are studied. The starch granules are irregular and large in hybrids and oval and small in inbred lines. The chain length, molecular weight, and crystallinity are significantly different among the samples. However, no distinct difference is observed between hybrids and inbred lines. The branching degree of hybrids (except THN2000) is significantly higher than that of inbred lines. The pasting, gelatinization, retrogradation temperatures, peak and breakdown viscosities, retrogradation enthalpy, and percentage are lower in inbred lines than in hybrids. By contrast, trough, final, and setback viscosities and gelatinization enthalpy are indistinctly different between the hybrids and inbred lines. Among the six hybrids, HTN2 is suitable to make glutinous food due to its high viscosity, whereas MTN2 may enable the production of food with minimal retrogradation. The high viscosity of JH1501 and the low retrogradation percentage of JSW15525 among the four inbred lines endow different advantages on quality breeding. Abstract : Sweet–waxy maize is a special type with recessive mutations of waxy gene and the disturbed sugar‐starch transition genes. The starch granules are large in hybrids and small in inbred lines, and the gelatinization temperatures, peak viscosity, retrogradation percentage are higher in hybrids. The results of the genotypic differences among the hybrids and inbred lines can suitable for various utilizations.